Processing-structure-property relationships of electrospun PLA-PEO membranes reinforced with enzymatic cellulose nanofibers. (January 2020) - Ghafari, Robab; Scaffaro, Roberto; Maio, Andrea; Gulino, Emmanuel F.; Lo Re, Giada; Jonoobi, Mehdi
Abstract: Three different solvent mixtures were used to prepare electrospun membranes based on polylactic acid (PLA), polyethylene oxide (PEO) and enzymatic cellulose nanofibers (CNF). The materials were characterized from a morphological, spectroscopic, mechanical and rheological point of view. Furthermore, swelling test were performed in order to assess the water uptake of each sample. The results put into evidence that the choice of the solvents affects the structure and the properties of the membranes. Among the protocols tested, using chloroform/acetone/ethanol mixture was found to allow a high degree of CNF dispersion and a good electrospinnability of polymer solutions. These features led to membranes with impressive improvement of mechanical properties (+350% in stiffness, +350% in tensile strength and +500% in toughness) with respect to those of PLA/PEO and dramatically increased the water uptake of these materials (up to +350% within 120 min). Highlights: Biodegradable polymers containing nanocellulose were electrospun into membranes. A proper choice of solvents is crucial to gather materials with different solubility. Three solvent mixtures were tested to allow electrospinnability and filler dispersion. Nanocellulose enhanced mechanical properties of membranes (up to +500%). Nanocellulose increased the water uptake of such membranes (up to +350%).